Managing logistics in sport: a comprehensive systematic literature review - Christoph Pott; Christian Spiekermann; Christoph Breuer; Michael ten Hompel (Management Review Quarterly, 2023)
Logistics and sport management are part of the globalized economy and interdisciplinary fields of science. Sporting events necessitate enormous logistical efforts by aiming to deliver certain tasks and materials at an exact time and a specific place in suitable quantity and quality. However, sport logistics not only is involved in the precise execution of events but deals with a wide range of topics. Sporting goods are transported along the supply chain to customers with economic objectives, stadium evacuation simulations are carried out using algorithms that originate in transportation logistics, and sport clubs are confronted with logistical issues both on their game days and during the rest of the year. A systematic literature review was undertaken to provide clarity regarding previous scientific endeavors and to offer orientation for interested practitioners. The authors propose a theoretical framework—the sport logistics triangle—that draws on the academic disciplines of logistics management and sport management and allows to classify all sport logistics activities. An in-depth categorization scheme and ten topic clusters illustrate how sport logistics has been studied thus far. Implications and research opportunities are elaborated for practitioners and scholars. The survey clearly underlines both the importance of sport logistics and its neglection in academics.
Keywords: L83; M10; R40; Z20; Z21; Z29; 650; Management; Logistics; Sport; Supply chain; Operations